Meibomian gland dysfunction – review - Nowińska, Anna; Wylęgała, Edward; Tarnawska, Dorota; Janiszewska, Dominika; Dobrowolski, Dariusz (Klinika Oczna / Acta Ophthalmologica Polonica, 2012)
Meibomian gland dysfunction is a common ocular disorder affecting from 39 to 50% of population. Despite that, so far a pathophysiology path of the disease remains unknown, moreover there is no distinct border between physiology and the disease. There has been no clear diagnostic criteria. The purpose of this review was to combine a current knowledge of Meibomian gland anatomy, Meibomian gland dysfunction epidemiology, as well as presenting current definition, nomenclature, classification and diagnostic criteria. The importance of diagnosis associated with conditions such as aqueous tear deficiency, seborrheic dermatitis, and rosacea is emphasized. The available treatment methods are discussed.